2000
DOI: 10.1177/000331970005100802
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms Used to Define the Short-Term Treatment with PGE1 in Patients with Intermittent Claudication and Critical Ischemia. The ORACL.E (Occlusion Revascularization in the Atherosclerotic Critical Limb) Study Group. The European Study

Abstract: Infusional, cyclic PGE1 treatment is effective in patients with intermittent claudication and critical limb ischemia (CLI). One of the problems related to chronic PGE1 treatment in vascular diseases due to atherosclerosis is to evaluate the variations of clinical conditions due to treatment in order to establish the number of cycles per year or per period (in severe vascular disease reevaluation of patients should be more frequent) needed to achieve clinical improvement. In a preliminary pilot study a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Good results were achieved with Alprostadil in the ICAI study [15] , and with Iloprost, as demonstrated in a meta-analysis by Loosemore and Dormandy [49]. Recently, interesting results were obtained with intermittent infusion of Iloprost [50], as well as of Alprostadil in the ORACLE Study [51], with a good cost/efficacy ratio.…”
Section: The Fate Of the Affected Limbmentioning
confidence: 99%
See 1 more Smart Citation
“…Good results were achieved with Alprostadil in the ICAI study [15] , and with Iloprost, as demonstrated in a meta-analysis by Loosemore and Dormandy [49]. Recently, interesting results were obtained with intermittent infusion of Iloprost [50], as well as of Alprostadil in the ORACLE Study [51], with a good cost/efficacy ratio.…”
Section: The Fate Of the Affected Limbmentioning
confidence: 99%
“…In patients for whom revascularization is not possible, or else it fails, an alternative is to try to modify the consequences of the low perfusion pressure on the distal microcirculation by some form of pharmacotherapy to reverse the rest pain and avoid amputation [2,14]. Prostanoids have been shown to have beneficial effects on most of the microcirculatory components by preventing the reciprocal potentiation of platelet activation, leukocyte activation and the damaged vascular endothelium; this is the reason why prostanoids have, in the last few years, been the most widely tested group of drugs in this condition [2,15,49,50,51]. Good results were achieved with Alprostadil in the ICAI study [15] , and with Iloprost, as demonstrated in a meta-analysis by Loosemore and Dormandy [49].…”
Section: The Fate Of the Affected Limbmentioning
confidence: 99%
“…At the moment there is important attention to, and new interest in, noninvasive treatment of peripheral vascular disease and its most disruptive complications due to ischemia and pain often leading to amputation. [4][5][6][7][8] In conclusion, local SWs treatment in severe CLI produced, in this preliminary study protocol, positive changes both in perfusion in the microcirculation (objectively detectable) and in pain.…”
Section: Discussionmentioning
confidence: 94%
“…The higher pressure was considered for the ORACLE score. [4][5][6][7][8] Microcirculatory measurements were performed and recorded at the dorsal part of the foot, at least 3 cm from skin lesions or ulcerations, necrosis, and toes. The measurements were made after 20 minutes of acclimatization and resting supine at 20°.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation